2006
DOI: 10.1103/physrevb.74.014202
|View full text |Cite
|
Sign up to set email alerts
|

Disorder and cluster formation during ion irradiation of Au nanoparticles inSiO2

Abstract: Au nanoparticles ͑NPs͒ have been formed by ion beam synthesis in 600 nm thin SiO 2. Subsequently the NPs were irradiated with 2.3 MeV Sn ions at liquid nitrogen temperature. Samples were analyzed using extended x-ray absorption fine structure ͑EXAFS͒ spectroscopy and small angle x-ray scattering ͑SAXS͒ as a function of Sn irradiation dose. Transmission electron microscopy shows that the NPs largely retain their spherical shape upon irradiation. However, we observe a reduction in average NP size and a concomita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…Comparing c-and a-Co NPs, the changes in all four structural parameters (CN , σ 2 , BL and C 3 ) are consistent with theoretical predictions for the amorphous phase of an elemental metal [71]. The trends in the structural parameters, including a BL expansion and a BL distribution skewed to longer BLs are in excellent agreement with recent investigations of ion irradiated Cu and Au NPs [67,72]. The aforementioned studies also report a decrease in the CN and a significant increase in the σ 2 (∼3 times larger than the bulk) in the disordered phase.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Comparing c-and a-Co NPs, the changes in all four structural parameters (CN , σ 2 , BL and C 3 ) are consistent with theoretical predictions for the amorphous phase of an elemental metal [71]. The trends in the structural parameters, including a BL expansion and a BL distribution skewed to longer BLs are in excellent agreement with recent investigations of ion irradiated Cu and Au NPs [67,72]. The aforementioned studies also report a decrease in the CN and a significant increase in the σ 2 (∼3 times larger than the bulk) in the disordered phase.…”
Section: Resultssupporting
confidence: 74%
“…The SHII-induced changes in these structural parameters with ion fluence are attributed to (i) and the increasing SBR for both the elongated and small NPs. Furthermore, the CN calculated from EXAFS is also sensitive to the fraction of atoms dispersed in the matrix as dimers/trimers [72] or in an oxidised state (ii) [46,124,125]. The fraction of oxidised atoms cannot be determined from the XTEM and SAXS analysis and are instead determined from the XANES analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Rizza et al [18] used 4 MeV Au + ions to irradiate Au NPs, the NPs are resolved into more uniform small ones. Similar phenomenon was observed in the experiment of irradiation of Au NPs by 2.3 MeV Sn ions [19].…”
Section: Controlling the Size And Distribution Of Nanoparticlessupporting
confidence: 71%
“…166 On the other hand, Cu NCs with a diameter of 8 nm were reported not to be amorphized, thus nicely showing where the limit for finite-size effects with respect to amorphization lies in this system. 166 The disordering of Au nanoclusters in silica was also examined 657,658 and it was shown that Au nanoclusters can be dissolved into Au monomers and very small clusters ͑dimers, trimers͒ in the SiO 2 matrix. On the other hand, irradiation of 3D arrays of about 3 nm diameter Co nanoparticles in silica with 90 and 150 keV Ar and characterization of them with Rutherford backscattering spectroscopy and magnetic methods indicated that these nanoparticles had a very high resistance to radiation damage, surviving damage up to 33 dpa.…”
Section: Metal Ncsmentioning
confidence: 99%